Treatment of brain metastases - Matzenauer, Marcel; Vrana, David; Melichar, Bohuslav (Biomedical papers, 2016)
Background: Brain metastases are a very common neurological sequela in cancer patients. The ability of current anti-cancer therapies to prolong overall survival is beleaguered by this development in the case of a number of different cancers. This review provides a general overview of relevant treatment modalities, highlights major decision strategies used in selecting the optimal treatment algorithm and summarizes important steps necessary before initiating therapy. Methods: A PubMed database search was done to identify publications describing the treatment of brain metastases including surgery, radiotherapy and symptomatic care. Results and Conclusion: Patient performance status and extent of disease play the most important roles in selecting between an aggressive or more conservative approach. As several other options are available, treatment decisions should be made in cooperation with multiple medical specialties and the involvement of multidisciplinary teams. In the future, brain metastases could become less of a treatment obstacle than they are today.
Keywords: Key words: brain; metastases; stereotactic; whole-brain; radiotherapy; radiosurgery; neurosurgery; chemotherapy